Logistics Management Awareness and the Implementation of Restaurant Business: An Application of Stepwise Multiple Regression - Trivedi, Akhilesh (Asian Administration and Management Review, 2019)
As logistics are at the heart of the operation of small and medium restaurants, the logistics management implementation of restaurant entrepreneurs is a critical component for achieving their business goals. Therefore, the purpose of this research was to find the factors influencing their logistics management implementation. A self-administrative questionnaire was used as a research tool in gathering data from 400 entrepreneurs who operated small and medium restaurants in Bangkok, Thailand. The research found that the restaurant entrepreneurs were aware of the logistics management at somewhat level. Finally, a stepwise multiple regression was conducted and predicted the tendency of logistics management implementation. The analysis provided the linear combination of six independent variables (entrepreneur’s gender, age, education, experience in business, size of business, and level of awareness in logistics management) which significantly related to the dependent variable (the tendency of logistics management implementation) at a statistical significance level of 0.05.